2020
DOI: 10.1161/atvbaha.120.314172
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Scaffolding Protein ENH (Enigma Homolog Protein) Promotes PHLPP2 (Pleckstrin Homology Domain and Leucine-Rich Repeat Protein Phosphatase 2)-Mediated Dephosphorylation of AKT1 and eNOS (Endothelial NO Synthase) Promoting Vascular Remodeling

Abstract: Objective: A decrease in nitric oxide, leading to vascular smooth muscle cell proliferation, is a common pathological feature of vascular proliferative diseases. Nitric oxide synthesis by eNOS (endothelial nitric oxide synthase) is precisely regulated by protein kinases including AKT1. ENH (enigma homolog protein) is a scaffolding protein for multiple protein kinases, but whether it regulates eNOS activation and vascular remodeling remains unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…The active component of Fructus Forsythiae is St John's wort, which could inhibit the uptake of serotonin, dopamine, and norepinephrine and delay the rapid ejaculation induced by serotonin agonists in a rat model [ 38 ]. Morinda officinalis has been proved to decrease the serum level of serotonin [ 39 ]. It was reported that the combination use of Radix Bupleuri and Radix Paeoniae Alba could increase serotonin, dopamine, and norepinephrine significantly in a chronic stress rat model [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The active component of Fructus Forsythiae is St John's wort, which could inhibit the uptake of serotonin, dopamine, and norepinephrine and delay the rapid ejaculation induced by serotonin agonists in a rat model [ 38 ]. Morinda officinalis has been proved to decrease the serum level of serotonin [ 39 ]. It was reported that the combination use of Radix Bupleuri and Radix Paeoniae Alba could increase serotonin, dopamine, and norepinephrine significantly in a chronic stress rat model [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several genes may play an important role in the process, including AKT1, EGFR, ESR1, ICAM1, IFNG, IL1B, IL6, MTOR, PTGS2, TNF. Nitric oxide synthesis by endothelial nitric oxide synthase is precisely regulated by protein kinases including AKT1 [44], and the quercetin from three herbs of QS formula has been revealed to suppress the protein level of pAKT1 [45].…”
Section: Discussionmentioning
confidence: 99%
“…In the drug-compound-target-pathway network, AKT1, MAPK1, RELA, TNF, and TP53 were the top ve targets with the highest degree value, which were the core targets of ZXF against ICH. Huang et al found that AKT1 can precisely regulate the synthesis of nitric oxide and further promote vascular remodeling [44]. In addition, AKT1 activation can promote the overexpression of glial cell-derived neurotrophic factor (GDNF) and thereby protect damaged neuronal cells [45].…”
Section: Discussionmentioning
confidence: 99%